Peningkatan Kreativitas Video Editing dengan Camtasia bagi Karang Taruna RW. 07 Perwira, Bekasi Utara, Jawa Barat - Akmaludin Akmaludin; Erene Gernaria Sihombing; Linda Sari Dewi; Ester Arisawati; Rinawati Rinawati; Wida Prima Mustika (Universitas Mathla'ul Anwar Banten, 2022)
IMPROVING VIDEO EDITING CREATIVITY WITH CAMTASIA FOR YOUTH ORGANIZATIONS RW 07 OFFICERS, NORTH BEKASI, WEST JAVA. Utilization of technology has become a mandatory requirement for users who want to develop their knowledge. The application of technology is not only on hardware but software is also growing rapidly which is balanced with the varied needs of users. Video editing is a form of development of software technology that plays a role in managing and producing works in the form of videos. Many video works are used in providing material delivery in the form of education, distance learning, and the development of new knowledge that is manifested in practical applications. Processing Video editing can use the Camtasia application or other applications. The editing application with Camtasia can be applied to the training of young people groups in the RW 07 Perwira officer village with the aim that training participants are able to make video editing with good editing standards, as well as create professionals who are able to create editing works that are full of creativity and understanding. in using animations, transitions, and effects to bring scine video to life. This training activity is supported by all authorized parties, both from the RW 07 Perwira office and from the activity committee in the form of community service. The results obtained from the Camtasia application training activities are in the form of mastery of material from all menu elements in the Camtasia application and creating professional young people groups in RW 07 Perwira with a short time in the form of community service.